EFEK MODERASI TRANSPARANSI PADA HUBUNGAN KONEKSI POLITIK TERHADAP PENURUNAN HARGA SAHAM - Christine Novita Dewi; Ellen Stefani; Dielanova Wynni Yuanita (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to empirically examine the effect of political connections on the risk of stock prices crashing. This study assessed a purposively selected sample of 62 companies listed on the Indonesia Stock Exchange for the 2019-2020 period. The method of data analysis using multiple linear regression shows that political connections can reduce the risk of stock prices crashing. The higher the political connections, the lower risk of crashing stock prices and vice versa. When companies with political connections present financial statements transparently, the risk of stock prices decreases. This research proves that when a company is unable to reduce its political connections, the transparency conducted by the company can reduce stock price risk.